2016
DOI: 10.1016/j.yebeh.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Hospital care for mental health and substance abuse in children with epilepsy

Abstract: Background Reducing the burden of pediatric mental illness requires greater knowledge of Mental Health and Substance Abuse (MHSA) outcomes in children who are at an increased risk of primary psychiatric illness. National data on hospital care for psychiatric illness in children with epilepsy are limited. Methods We used the Kids’ Inpatient Database (KID), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality, from 2003-2009 to examine MHSA hospitalization patterns in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Patients with physical illness are at increased risk for suicide. [5][6][7] Suicide is the fourth most frequently reported sentinel event to The Joint Commission, with a significant percentage of these deaths occurring in nonbehavioral health care units, such as medical and surgical units, the ICU, and the emergency department (ED). 8 In 2016, The Joint Commission issued Sentinel Event Alert 56, recommending that all medical patients be screened for suicide risk because medical settings provide an optimal venue for identifying youth at risk.…”
mentioning
confidence: 99%
“…Patients with physical illness are at increased risk for suicide. [5][6][7] Suicide is the fourth most frequently reported sentinel event to The Joint Commission, with a significant percentage of these deaths occurring in nonbehavioral health care units, such as medical and surgical units, the ICU, and the emergency department (ED). 8 In 2016, The Joint Commission issued Sentinel Event Alert 56, recommending that all medical patients be screened for suicide risk because medical settings provide an optimal venue for identifying youth at risk.…”
mentioning
confidence: 99%
“…2,60 As the psychological and neurobiological sequelae of chronic physical illness are increasingly recognized, the contribution from mental health care providers to medically ill pediatric patients is being increasingly recognized and formalized, particularly among certain illnesses, such as pediatric cancers, epilepsy, cystic fibrosis, and sickle cell disease. [60][61][62][63] For instance, the Cystic Fibrosis Foundation and European Cystic Fibrosis Society recently partnered to produce consensus guidelines on implementing developmentally appropriate psychoeducation and screening for anxiety and depression in cystic fibrosis patients and their caregivers, as well as recommendations for specific treatments, such as cognitive behavioral therapy, selective serotonin reuptake inhibitor medications, and benzodiazepines. 64 Kazak and colleagues composed a recent literature review demonstrating the need for routine, systematic assessments of psychosocial needs in children and caregivers with cancer, 65 while the international Posterior Fossa Society determined in a recent consensus meeting that identification and treatment of emotional and behavioral morbidities in this population is an important avenue for upcoming work.…”
Section: Considerations In Medically Ill Childrenmentioning
confidence: 99%
“…In adolescent studies, it is indicated that children with neurological diseases such as epilepsy had greater odds of bipolar disorder, psychosis and suicide attempt/ideation (Thibault et al, 2016). Moreover, there are studies showing that the presence of disease of any organ or physical system significantly increases the risk of subsequent suicide, regardless of gender, individual psychiatric background or socio-economic status (Qin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%